Broad spectrum activity of the checkpoint kinase 1 inhibitor prexasertib as a single agent or chemopotentiator across a range of preclinical pediatric tumor models - Lowery, Caitlin D. (Clin Cancer Res, 2018)
PURPOSE: Checkpoint kinase 1 (CHK1) inhibitors potentiate the DNA damaging effects of cytotoxic therapies and/or promote elevated levels of replication stress, leading to tumor cell death. Prexasertib (LY2606368) is a CHK1 small molecule inhibitor under clinical evaluation in multiple adult and pediatric cancers. In this study, prexasertib was tested in a large panel of preclinical models of pediatric solid malignancies alone or in combination with chemotherapy. EXPERIMENTAL DESIGN: DNA damage and changes in cell signaling following in vitro prexasertib treatment in pediatric sarcoma cell lines were analyzed by western blot and high content imaging. Anti-tumor activity of prexasertib as a single agent or in combination with different chemotherapies was explored in cell line-derived (CDX) and patient-derived xenograft (PDX) mouse models representing nine different pediatric cancer histologies. RESULTS: Pediatric sarcoma cell lines were highly sensitive to prexasertib treatment in vitro, resulting in activation of the DNA damage response. Two PDX models of desmoplastic small round cell tumor and one malignant rhabdoid tumor CDX model responded to prexasertib with complete regression. Prexasertib monotherapy also elicited robust responses in mouse models of rhabdomyosarcoma. Concurrent administration with chemotherapy was sufficient to overcome innate resistance or prevent acquired resistance to prexasertib in preclinical models of neuroblastoma, osteosarcoma, and Ewing’s sarcoma, or alveolar rhabdomyosarcoma, respectively. CONCLUSION: Prexasertib has significant anti-tumor effects as a monotherapy or in combination with chemotherapy in multiple preclinical models of pediatric cancer. These findings support further investigation of prexasertib in pediatric malignancies.